Drug Delivery: Electrodeless Reverse Electrodialysis Patches as an Ionic Power Source for Active Transdermal Drug Delivery (Adv. Funct. Mater. 15/2018). (14th April 2018) - Kwon, Seung‐Ryong; Nam, So Hee; Park, Clara Yongjoo; Baek, Seol; Jang, Joomyung; Che, Xiangguo; Kwak, Su Hong; Choi, Yu‐Ra; Park, Na‐Rae; Choi, Je‐Yong; Lee, Yan; Chung, Taek Dong
Abstract : Yan Lee, Taek Dong Chung, and co‐workers report a new strategy for active transdermal drug delivery using electrodeless reverse electrodialysis (RED) patches in article number1705952 . The ionic‐flow‐based RED patch pumps impermeable, charged drugs through the skin layer with high efficiency without any electrolysis. The electronics‐free RED can provide a biocompatible, flexible, and eco‐friendly power source for operating various wearable devices.